2013
DOI: 10.1007/s00421-013-2784-7
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids improve high-intensity exercise performance in humans

Abstract: Short-term dexamethasone administration increases high-intensity one-legged kicking time to exhaustion and 20-m shuttle run performance, although sprint ability and the initial loss of muscular force generating capacity are similar after DEX and placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 26 publications
1
38
0
5
Order By: Relevance
“…The vast majority of literature on muscle GR signaling has focused on muscle wasting, a side effect of excessive or sustained GC exposure that is mediated, in part, by direct GR-dependent transactivation of genes that drive myocyte atrophy (e.g., Foxo3a, Gdf8/Myostatin, Fbxo32/Atrogin1; also known as atrogenes) (1,2). However, literature dating back to the 1930s, including the classic physiological studies from the laboratory of Dwight Ingle (3,4), have documented that moderate or transient exposure to GCs can enhance muscle performance and produce ergogenic effects in animals and humans (5)(6)(7)(8)(9)(10)(11)(12)(13). Consistent with this known physiological role of GCs in anticipatory metabolic adaptation, surreptitious GC ingestion is a well-known doping strategy used by elite endurance athletes, an act that has prompted disqualifications and has led to the universal banning of these drugs by sports regulatory agencies (14).…”
mentioning
confidence: 99%
“…The vast majority of literature on muscle GR signaling has focused on muscle wasting, a side effect of excessive or sustained GC exposure that is mediated, in part, by direct GR-dependent transactivation of genes that drive myocyte atrophy (e.g., Foxo3a, Gdf8/Myostatin, Fbxo32/Atrogin1; also known as atrogenes) (1,2). However, literature dating back to the 1930s, including the classic physiological studies from the laboratory of Dwight Ingle (3,4), have documented that moderate or transient exposure to GCs can enhance muscle performance and produce ergogenic effects in animals and humans (5)(6)(7)(8)(9)(10)(11)(12)(13). Consistent with this known physiological role of GCs in anticipatory metabolic adaptation, surreptitious GC ingestion is a well-known doping strategy used by elite endurance athletes, an act that has prompted disqualifications and has led to the universal banning of these drugs by sports regulatory agencies (14).…”
mentioning
confidence: 99%
“…In untrained men, one-legged knee-extensor exercise time to exhaustion was not affected by 5 days of dexamethasone [116]. In contrast, using a similar dosing scheme, another study found an increase in one-legged knee-extensor exercise time to exhaustion of 29%, and running distance in a certain type of maximal exercise test, namely 20-m shuttle-run test, of 19% [117]. Sprint performance over 30 m was not affected in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Training associated with glucocorticoid treatment resulted in an 80% improvement in time‐to‐exhaustion performance after 1 week, as well as decreases in adrenocorticotrophic hormone, dehydroepiandrosterone, prolactin, growth hormone, and thyroid‐stimulating hormone, free testosterone, and increase in blood glucose concentration. Similarly, Casuso et al [59] assessed muscle function after a 5‐day ingestion period (twice/day) of either 2 mg of dexamethasone or placebo, but in a one‐legged kicking exercise, and whole‐body exercise performance, using 20‐m shuttle run and 30 m sprint tests. One‐leg kicking exercise time‐to‐exhaustion was longer and total running distance in the 20‐m shuttle run test was improved.…”
Section: Resultsmentioning
confidence: 99%